ANALYSIS OF NETWORKS IN ELECTRICAL DISTRIBUTION SYSTEMS USING FAULT TREE ANALYSIS METHOD IN PLN (PERSERO) UP3 BULUKUMBA ULP PANRITA LOPI - Riswandi, Riswandi; Sa'ban Miru, Alimuddin; Firdaus, Firdaus (Journal of Electrical Engineering and Informatics, 2024)
Distribution of electricity is often interrupted which can result in the process of distribution of power to the consumer becoming abnormal. Therefore, an analysis of the cause of disturbance of the electricity distribution network needs to be carried out. This research is conducted using the method of Fault Tree Analysis (FTA) because it is an effective method in determining the cause of the disturbance and with the help of Microsoft Exel as well as manual calculations. The results of the research obtained that which is the main factor that causes the occurrence of the disruption in the system of distribution of electric energy in PT PLN (Persero) UP3 Bulukumba ULP Panrita Lopi is due to disruptions in the distribution equipment, animal activity, human activity, material interference, error of installation and nature interferences. From the results of the study, it can be concluded that there are six factors that cause the disturbance of the process of electricity distribution to consumption, then become a priority for PLN based on the percentage of disruption occurred.